1977
DOI: 10.1093/nar/4.9.3259
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination of 6-methyluracil and its nucleosides

Abstract: 6-Methyluracil and its perbenzoylated 1-(beta-D-ribofuranosyl) and 1-(2-deoxy-beta-D-ribofuranosyl) derivatives afford on treatment with elemental fluorine in acetic acid solutions, the corresponding derivatives of 5-fluoro-6-methyluracil and 5-fluoro-6-fluoromethyluracil. The free nucleosides have been obtained from the protected derivatives by methanolysis. The CH2F linkage in 5-fluoro-6-fluoromethyluracil derivatives is stable towards hydrolysis and nucleophilic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…52 To""" U.d" 2' position. It has already been shown that 2',5'-di-0-benzoyl-02,3'-cyc!ouridine (190) can be rearranged on heating to afford the 02,2'-cyc!0 derivative (192) through the 2/,3'-benzoxonium ion intermediate (191). ( 190 Ph 192 191 The finding that l-(p-o-arabinofuranosyl)cytosine (araC) possessed antitumor activity prompted several efforts to improve on the synthesis of araC.…”
Section: /mentioning
confidence: 98%
See 2 more Smart Citations
“…52 To""" U.d" 2' position. It has already been shown that 2',5'-di-0-benzoyl-02,3'-cyc!ouridine (190) can be rearranged on heating to afford the 02,2'-cyc!0 derivative (192) through the 2/,3'-benzoxonium ion intermediate (191). ( 190 Ph 192 191 The finding that l-(p-o-arabinofuranosyl)cytosine (araC) possessed antitumor activity prompted several efforts to improve on the synthesis of araC.…”
Section: /mentioning
confidence: 98%
“…(188) For other direct fluorinations, fluorine in pyridine-Freon-II at -78°C was reported to be effective for the preparation of 5-fluorouridine. (189) Fluorine in acetic acid followed by treatment with triethylamine was also efficient as demonstrated in the preparation of 5-fluoro-6-methyluridine and its 2'-deoxy derivative, (190) as well as various 2' -substituted 2' -deoxyurdines. (191) Formation of 5-fluoro-6-fluoromethyluridine was observed in the fluorination of 6-methyluridine, which was stable in the deprotection step.…”
Section: Halogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Schuman et al [3] patented a procedure for the synthesis of 5-fluoro-6-methyluracil by fluorination of 6-methyluracil with gaseous fluorine in water. Cech et al [4] later obtained 5-fluoro-6-methyluracil by the action of fluorine on 6-methyluracil in acetic acid, and the authors noted that no 5-fluoro-6-methyluracil was formed when acetic acid was replaced by water. Elemental fluorine was widely used to synthesize a number of other fluorinated uracils (see, e.g., [4,5]).…”
mentioning
confidence: 99%
“…Cech et al [4] later obtained 5-fluoro-6-methyluracil by the action of fluorine on 6-methyluracil in acetic acid, and the authors noted that no 5-fluoro-6-methyluracil was formed when acetic acid was replaced by water. Elemental fluorine was widely used to synthesize a number of other fluorinated uracils (see, e.g., [4,5]). In addition, such fluorinating agents as OF 2 [6], AcOF [7,8], CF 3 OF [9,10], XeF 2 [11], and CsSO 4 F [12] were used.…”
mentioning
confidence: 99%